Univariate and multivariate GARCH models applied to Bitcoin futures option pricing - Pierre J. Venter; E. Maré (Journal of Risk and Financial Management, 2021)
In this paper, the Heston-Nandi futures option pricing model is applied to Bitcoin futures options. The model prices are compared to market prices to give an indication of the pricing performance. In addition, a multivariate Bitcoin futures option pricing methodology based on a multivatiate GARCH model is developed. The empirical results show that a symmetric model is a better fit when applied to Bitcoin futures returns, and also produces more accurate option prices compared to market prices for two out of three expiry dates considered.
Keywords: 330; Bitcoin; futures options; GARCH; multivariate